KORELASI KEBIASAAN MEMBACA DENGAN KEMAMPUAN MENULIS ARTIKEL MAHASISWA JURUSAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS NEGERI MEDAN - RUMASI SIMAREMARE (BAHAS, 2012)
This research study contributes to ability to understand the ability to read articels. The population of this study are all students of Department of Languages an Literature of Indonesia, with  a sample of 40 people who had been assigned randomly/rendom technique of the population. The resesearch instrument used was a questionari form an objective reading ability as mucah as 40 question form and test the ability to create articles of 500 words. The realize the above objetives, this study used the descriptive methid ( a method that attempt to slove one answer to the problems being faced at present) correlational statistical analysis trough a formula of Pearson Product r and the formula coefficient of determination . Based on data analysis techniques, the research found, there was a positve and significant reading habits with students writing articles Indonesian Language and Literatur, State University of Medan.  This show better the reading habits of students, it will cause increasing students ability to write articles Indonesian Language and Literature, State University of Medan. The average Department of FBS Unimed is 74.2 category of B (Good). The average value of students ability to understand article Department of Language and Literature, State University of Medan is 77.8 category very good. Correlation test result showed that reading significant correlation with the ability to undertsand the article in the 5% significance level is r calculate > r tabel that is 0.396<0.67> 0.505, wich means that there is a significant positve relationship habits of reading on the ability of the ability   to write article.